2022
DOI: 10.3390/diagnostics12010137
|View full text |Cite
|
Sign up to set email alerts
|

First Case of COVID-19 Treated with Monoclonal Anti-Spike Antibodies in a Patient with Cystic Fibrosis in Romania

Abstract: Patients with chronic lung conditions, including cystic fibrosis, may be prone to severe COVID-19. Therefore, therapeutic intervention should be prompt and tailored to all associated comorbidities. We report the case of a 17-year-old male adolescent with cystic fibrosis and multiple chronic conditions (bronchiectasis, exocrine pancreatic insufficiency, chronic multidrug resistant Pseudomonas aeruginosa colonization, nasal polyposis, chronic sinusitis, ventricular extrasystoles and multiple drug allergies), who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A total of 31 papers published as observational studies reported an association of COVID-19 in patients with CF [ 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] ( Table 1 ). These studies comprised 661,386 patients in total, including children, adults, and elderly age groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 31 papers published as observational studies reported an association of COVID-19 in patients with CF [ 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] ( Table 1 ). These studies comprised 661,386 patients in total, including children, adults, and elderly age groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, only 19,150 (2.9%) patients were diagnosed with CF and, from these patients, 2523 (0.4%) were diagnosed with both CF and COVID-19. Regarding patients with CF and COVID-19, the sex proportion was (female/male) 1207/1167 [ 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 45 , 47 , 48 , 49 , 50 ]. Some publications [ 21 , 26 , 35 , 40 , 46 ] did not report the sex of the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…antigen presenting cells, lymphocytes, myeloid cells, etc. ), it does represent an arm of the complex protection system so heavily relied upon in this pandemic; and, indeed, infusion of spike Ab (casirivimab, imdevimab, regdanvimab) only has proven effective treatment for people with CF [ 29 ]. Our data show persistent IgG after vaccination or natural infection in pwCF is detectable for up to 13 months.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the burden on the hospitals, outpatient departments, also called "infusion clinics," as well as mobile units were created (Ton et al, 2021;Tulledge-Scheitel et al, 2021). Here, patients at high-risk for progression to severe COVID-19 were treated with NAbs as early as possible after symptom onset, with good clinical response and lower rates of hospitalization or requirement for supplemental oxygen (Al-Obaidi et al, 2022;Kwak et al, 2022;Stan et al, 2022). At that point in the pandemic, antivirals were considered "rescue therapy" and used only in cases where NAbs had either not been administered, or in cases of progression to pneumonia despite NAb treatment.…”
Section: Neutralizing Anti-spike Protein Antibodiesmentioning
confidence: 99%